Augmented Reality (AR) for Deaf and Hard of Hearing (DHH) for animation / Mohamad Saifuddin Rusli and Zainuddin Ibrahim - Rusli, Mohamad Saifuddin; Ibrahim, Zainuddin (2022)
Augmented Reality (AR) technology in education faces a significant gap, especially for deaf and hard-of-hearing (DHH) students. Research has shown the vast growing technologies for AR in many sectors; however, implementing the technologies towards education for DHH students is still lacking in Malaysia. This study aims to provide a rationale and justification for using AR technologies for DHH students for Animation. Based on the literature review, five important keys drive the research questions. For the context of this paper, the three considerable keys are AR as a teaching aid (1), the importance of Art and Design (2), and social stigma (3). These primary keys are to support and justify this research. An interview was conducted with teachers who teach DHH students to further help the three primary keys. An interview with the AR developer was also conducted for this research. The study developed an AR with Animation based on the interview and record-keeping. The results show that implementing this technology will significantly impact DHH students, especially in Art and Design. When exploring and using the AR Application, DHH students felt awkward. They were unfamiliar with the use of AR applications in their class. Nevertheless, they all enjoyed using it as it will have vast potential and possibility. As technology grows, DHH students will be one step ahead of others. It is worth mentioning the social stigma among them and how future research would continue to diminish the social stigma.